Identity: a cohesive device in some Persian live sport radio and TV talks (Acta Scientiarum. Language and Culture, 2017)
Identity is a cohesive device that helps to have a better understanding of speech. This article analyzes the identity device and its sub-sets in some Persian live sport radio and TV programs. The theoretical framework of this research is Dooley and Levinsohn (2001). A data-driven approach based on the access to the detailed discourse context was used to have a reliable sample for the research. So, around 200 minutes of 20 different live sport radio and TV programs were transcribed. The authors present the identity extent of functionality via comparing its degree of frequency employing the SPSS software while evaluating the meaningfulness of differences in application of each of its sub-categories. This evidence-oriented research supports that the subcategories of identity can also be studied in Persian in the same way as Dooley and Levinsohn’s (2001) view among which pronouns receive the most frequency whereas pro-forms do the least. Pronouns and ellipsis contain a meaningful difference between their application in radio and TV data. In addition, there is not any significant difference between the applications of repetition, substitution and other pro-forms. Finally, identity is reported as having a significant relation in its application in the research corpora.